MENJAGA INTEGRITAS DEMOKRASI LOKAL TERHADAP PERSOALAN NETRALITAS ASN DALAM PEMILU DAN PILKADA - Aldi Afrihadi; Feni Rosalia; Syarief Makhya; Maulana Mukhlis (Journal Publicuho, 2025)
This research aims to analyze conflicts related to the neutrality of the State Civil Apparatus (ASN) in the context of elections and post-conflict regional elections in Indonesia, with a focus on sources of conflict, dynamics and management strategies for preventing and handling conflicts. The methods used include literature studies, citing media interviews, and ASN observations in several regions involved in the election process. The research results show that conflicts related to ASN neutrality originate from structural inequality in the bureaucracy, differences in values between professionalism and political patronage, as well as conflicts of interest between demands for neutrality and political pressure. In conclusion, preventing and handling conflicts related to ASN neutrality requires a comprehensive approach involving structural reform of the bureaucracy, transformation of organizational culture, and active participation of civil society. Implementing appropriate conflict management strategies will not only strengthen the integrity of ASN, but also support a more transparent and accountable democratic process in Indonesia.